PENINGKATAN KETERAMPILAN MEMBACA INTENSIF DENGAN MENGGUNAKAN PEMBELAJARAN KOOPERATIF STRATEGI KWL PADA SISWA KELAS III SDN KALIWUNGU 1 KECAMATAN KALIWUNGU KABUPATEN SEMARANG - Suprapti Suprapti; Hendri Rasminto (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
This study used a classroom action research design which was carried out in three stages, namely the pre-cycle stage, cycle I, and cycle II with the research subjects being grade III students at SDN Kaliwungu 1. This study used two variables, namely intensive reading skills and intensive reading learning using the KWL strategy. . Pre-cycle data collection was done by using the test technique, while in the first cycle and the second cycle using the test and non-test technique. Non-test instruments in the form of observations, journals, interviews, and documentation. Data analysis includes quantitative and qualitative data. The results showed that after participating in intensive reading learning using the KWL strategy, the average value of intensive reading skills of third grade students at SDN Kaliwungu 1 increased. The average value of intensive reading using the KWL strategy achieved by students in the pre-cycle was 56 and in the first cycle it increased to 65 or 9% then in the second cycle it increased to 76 or 11%. Changes in attitudes and behavior of third grade students at SDN Kaliwungu 1 Kaliwungu District, Semarang Regency have increased towards a better direction, namely students are more active and enthusiastic in learning, because students are starting to enjoy and enjoy intensive reading learning using the KWL strategy.